Caracterización de una turbina eólica de eje vertical tipo híbrida utilizando dinámica de fluidos computacional (2020)
In the last decades, wind energy has generated lost of interest from science community because it is a clean, renewable alternative with little environmental impact to global warming in terms of energy global demand. Moreover, because of its versatility and performance, it is usually considered to evaluate more economic and sustainable methods which supply energetic deficit in isolated zones of the world. In this work, a efficiency analysis of a vertical axis wind turbine is made. The turbine could be used to contribute as a solution of the energetic problem that the country has. The efficiency analysis has satisfactory results which means that the characterization of the turbine is good.